Bioactivity profiling of mycelial extract of Volvariella volvacea (Bull.) Singer (paddy straw mushroom) from the Philippines - Emmily Asasira; Sofronio P. Kalaw; Angeles M. De Leon; Rich Milton R. Dulay (Italian Journal of Mycology, 2025)
Volvariella volvacea (paddy straw mushroom) is an edible and nutritious mushroom. This study highlights the chemical compositions, antioxidant, antibacterial, and teratogenic activities of mycelial extracts of the V. volvacea (PQ671094 and PQ671093) isolates from San Jose and La Union, Philippines. The molecular identities of mushrooms were confirmed using the ITS region of rDNA. Mycelia of both isolates contained essential oil, sugar, and coumarin. Phenol, fatty acid, anthrone, and alkaloid were detected only in La Union isolate, whereas flavonoid was only found in San Jose isolate. San Jose mycelial extract recorded radical scavenging activity (RSA) of 81.34%, whereas La Union mycelial extract had 79.69% RSA. In disc-diffusion assay, only La Union isolate extract exhibited antibacterial activity with a diameter zone of inhibition of 10.49 mm against Staphylococcus aureus. In both extracts, 100% mortality of zebrafish embryos was registered at 10000 ppm extract at 12-hour post-treatment exposure (hpte), and at 1000 ppm extract at 48-hpte, indicating that extract concentration and time exposure dependent. Embryos at 10 ppm to 100 ppm extract of both isolates significantly decreased the hatchability, while embryos exposed to 1 ppm to 100 ppm extract showed lower heartbeat rates. Teratogenic effects, including tail malformation, head malformation, yolk deformity, pericardial oedema, reduced pigmentation, and delayed growth, were observed at 10 ppm and 100 ppm of both extracts. Altogether, V. volvacea mycelia contain mycochemicals and exhibit antioxidant, antibacterial and teratogenic properties.